Constituents from Apium graveolens and their anti-inflammatory effects. Issue 11 (2nd November 2017) - Zhu, Li-Han; Bao, Tian-Hui; Deng, Yue; Li, Hua; Chen, Li-Xia
Abstract: A phthalide glycoside, (3 R, 4 R )-4- O - β -D-glucopyranosyl-senkyunolide (1 ), and a megastigmane glycoside, (6 S, 7 R )-3-oxo-megastigma-4, 8-dien-7- O - β -D-glucoside (2 ), along with two known aglycones (3–4 ), were isolated from the 70% EtOH extract of fresh whole grass of Apium graveolens L. Their structures were elucidated by extensive spectroscopic analysis. All of these compounds were tested for their inhibitory effects on nitric oxide (NO) production in the RAW 264.7 macrophages. Among them, compounds3 and4 showed potent inhibitory activity against LPS-induced nitric oxide production in RAW 264.7 macrophages, with IC50 values of 24.0 ± 2.1 μM and 28.6 ± 2.4 μM, respectively. Abstract :